Factors affecting the event of premium delivery - Siska Suci Triana Ginting (Universitas Aisyah Pringsewu, 2022)
Premature/premature delivery is still a problem in the world, including Indonesia, related to prevalence, perinatal morbidity and mortality, which is the main cause of infant mortality and the second cause of death after pneumonia in children under five years of age. This study aims to determine the factors influencing the incidence of preterm labor in Rsia Stella Maris Medan in 2022. Methods: This type of research is a descriptive study, with a cross-sectional design. Sampling was done by systematic random sampling, where the sample in this study was 64 respondents. Data collection techniques using a questionnaire sheet. Bivariate analysis technique using chi-square test. Results: most of the incidence of childbirth with age 20-35 years as many as 40 respondents (59.4%) almost most of the incidence of childbirth with parity 5 times as many as 38 respondents (32.9%), most of the incidence of childbirth with There have been 35 respondents (54.7%) preterm deliveries, most of them 44 respondents (68.8%). 68.8%), most of the incidences of childbirth with pregnant women experiencing preeclampsia/eclampsia were (56.2%) and most of the pregnancies with twin pregnancies were pregnant women with singleton pregnancies as many as 36 respondents (56.2%). Conclusion: There is a relationship between age, parity, history of preterm labor, PROM, Placenta Previa, Preeclampsia/Eclampsia, and Twin Pregnancy Affecting Premature Delivery in Rsia Stella Maris Medan in 2022.Abstrak: Persalinan prematur/prematur masih menjadi masalah di dunia termasuk Indonesia terkait prevalensi, morbiditas dan mortalitas perinatal yang merupakan penyebab utama kematian bayi dan penyebab kematian kedua setelah pneumonia pada anak balita. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi kejadian persalinan prematur di Rsia Stella Maris Medan tahun 2022. Metode: Jenis penelitian ini adalah penelitian deskriptif, dengan desain cross sectional. Pengambilan sampel dilakukan dengan sistematik random sampling, dimana sampel dalam penelitian ini sebanyak 64 responden. Teknik pengumpulan data menggunakan lembar angket. Teknik analisis bivariat menggunakan uji che square. Hasil: sebagian besar kejadian persalinan dengan usia 20-35 tahun sebanyak 40 responden (59,4%) hampir sebagian besar kejadian persalinan dengan paritas 5 kali sebanyak 38 responden (32,9%), sebagian besar kejadian persalinan dengan persalinan preterm sebanyak 35 responden (54,7%), sebagian besar 44 responden (68,8%). 68,8%), sebagian besar kejadian persalinan ibu hamil mengalami preeklampsia/eklampsia sebanyak (56,2%) dan sebagian besar ibu hamil dengan kehamilan kembar adalah ibu hamil dengan kehamilan tunggal sebanyak 36 responden (56,2%). Kesimpulan: Bahwa ada hubungan usia, paritas, riwayat persalinan prematur, KPD, Plasenta Previa, Preeklampsia/Eklampsia, Kehamilan Kembar yang Mempengaruhi Persalinan Prematur di Rsia Stella Maris Medan Tahun 2022